Virilization of a young girl caused by concomitant ectopic and intra-adrenal adenomas of the adrenal cortex - Choukair, Daniela; Beuschlein, Felix; Zwermann, Oliver; Wudy, Stefan A.; Haufe, Sabine; Holland-Cunz, Stefan; Bettendorf, Markus (Hormone research in paediatrics, 2013)
Background: Adenomas of the adrenal gland are rare causes of virilization in childhood. Case Report: A girl aged 2 years and 4 months presented with pubarche, distinct clitoral hypertrophy, tall stature, and increased height velocity. Plasma testosterone and dehydroepiandrosterone were elevated. Androgens remained unchanged after adrenocorticotropic hormone, and dexamethasone administrations. Ultrasound examination and magnetic resonance imaging indicated an extra-adrenal mass adjacent to the left adrenal gland, which was removed by endoscopic surgery. However, plasma androgens remained elevated and 131I-iodomethyl-norcholesterol scintigraphy revealed tracer enhancement in the right adrenal gland, which was consecutively removed. Virilization regressed after extirpation of the adenomas and height velocity normalized. Results: Histology revealed a circumscribed adenoma in the right adrenal gland and an epithelial mass with adrenal cortical cells in the left-sided ectopic tumor. In the ectopic tumor, melanocortin 2 receptor expression was augmented threefold compared to the control, indicating adrenal origin. Conclusions: In this young girl, virilization is due to concomitant ectopic and intra-adrenal adenomas of the adrenal cortex. By melanocortin 2 receptor expression, it was confirmed that the ectopic adenoma derived from the adrenal cortex. Specific scintigraphy, if available, assists in allocating the source of androgen hypersecretion.